EMPOWERING GENERATION Z: THE IMPACT OF ATTITUDES TOWARDS SOCIAL AWARENESS AND SOCIAL INNOVATION ON SOCIAL ENTREPRENEURIAL INTENTION IN MALAYSIA - Siti Shalima Sabri; Siti Asma Mohd Rosdi @ Mohd Rodhi, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Social entrepreneurs possess a strong drive and determination as they tackle important social problems by introducing innovative ideas with the goal of making big changes in society. The aim of this research is to improve the ability of the Z generation to become proactive and influential social entrepreneurs by promoting awareness and education about social entrepreneurship. The study encompasses three variables: social entrepreneurial intention (SEI), social innovation (SI), and attitude towards social awareness (ATSA). This study employed a quantitative methodology. An online questionnaire was used to collect data from a sample of 420 university students, both from public and private institutions, in Malaysia. The participants were between the ages of 18 and 30. The study employed a simple random sampling technique. The acquired data were classed, coded, and analysed using the SPSS and Smart PLS software. The R2 score of approximately 80% indicates that the model well captures the range of variability in SEI. This indicates that the model is appropriate for future research endeavours. The results indicate that ATSA (β=0.266, t=3.108, p<0.002), SI (β=0.578, t=6.754, p<0.000), ATSA and SI (β=0.458, t=6.398, p<0.00), and ATSA, SI, and SEI (β=0.458, t=6.398, p<0.000) have an important effect on SEI among Z-Generation individuals in Malaysia. Overall, this study highlights the importance of promoting (ATSA) and (SI)to impact (SEI) among the Z-Generation in Malaysia. This study suggests that it is crucial for the government to cultivate a culture that prioritizes social entrepreneurship through educational programs, financial resources, and regulatory assistance. The Z-Generation recognizes the significance of cultivating social awareness, inventiveness, and community participation. These qualities equip them with the necessary skills to address social issues and make a positive impact on society's change.